Vesicles from different Trypanosoma cruzi strains trigger differential innate and chronic immune responses. Issue 1 (26th November 2015) - Nogueira, Paula M.; Ribeiro, Kleber; Silveira, Amanda C. O.; Campos, João H.; Martins‐Filho, Olindo A.; Bela, Samantha R.; Campos, Marco A.; Pessoa, Natalia L.; Colli, Walter; Alves, Maria J. M.; Soares, Rodrigo P.; Torrecilhas, Ana Claudia
Abstract : Trypomastigote forms of Trypanosoma cruzi, the causative agent of Chagas Disease, shed extracellular vesicles (EVs) enriched with glycoproteins of the gp85/ trans ‐sialidase (TS) superfamily and other α‐galactosyl (α‐Gal)‐containing glycoconjugates, such as mucins. Here, purified vesicles from T. cruzi strains (Y, Colombiana, CL‐14 and YuYu) were quantified according to size, intensity and concentration. Qualitative analysis revealed differences in their protein and α‐galactosyl contents. Later, those polymorphisms were evaluated in the modulation of immune responses (innate and in the chronic phase) in C57BL/6 mice. EVs isolated from YuYu and CL‐14 strains induced in macrophages higher levels of proinflammatory cytokines (TNF‐α and IL‐6) and nitric oxide via TLR2. In general, no differences were observed in MAPKs activation (p38, JNK and ERK 1/2) after EVs stimulation. In splenic cells derived from chronically infected mice, a different modulation pattern was observed, where Colombiana (followed by Y strain) EVs were more proinflammatory. This modulation was independent of the T. cruzi strain used in the mice infection. To test the functional importance of this modulation, the expression of intracellular cytokines after in vitro exposure was evaluated using EVs from YuYu and Colombiana strains. Both EVs induced cytokine production with the appearance of IL‐10 in the chronically infected mice. A high frequency of IL‐10 in CD4+ and CD8+ T lymphocytes was observed. A mixed profile of cytokine induction was observed in B cells with the production of TNF‐α and IL‐10. Finally, dendritic cells produced TNF‐α after stimulation with EVs. Polymorphisms in the vesicles surface may be determinant in the immunopathologic events not only in the early steps of infection but also in the chronic phase.